ANALISIS TERHADAP FUNGSIONALISASI LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN - Eman Sulaiman (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2015)
Birth of the Witness and Victim Protection Agency (Agency) is the fruit of the reform movement. Itspresence is not actually to bring a new mission. The existence of the Agency be necessary presence ,to support law enforcement in Indonesia . Vision, Mission and work program of the Agency into asystemic one thing that must be supported by a comprehensive implementation rules. The whole rangeof the Agency must first have an understanding as well as the high professionalism of this institutionand understand the true nature of man which can never be expected to improve society and theenvironment let alone in the scale of the nation. Likewise, the presence of these institutions must havethe suppor of all elements of the nation in order to function in society.